2008
DOI: 10.1183/09031936.00009208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucocorticoids in ventilated piglets with severe pneumonia

Abstract: There is clinical evidence suggesting that glucocorticoids may be useful in severe pneumonia, but the pathogenic mechanisms explaining these beneficial effects are unknown.The aim of the present study was to determine the effects of adding glucocorticoids to antibiotic treatment in an experimental model of severe pneumonia.In total, 15 Lagerwhite-Landrace piglets were ventilated for 96 h. After intubation, a 75 mL solution containing Pseudomonas aeruginosa (10 6 cfu?mL -1 ) was bronchoscopically inoculated.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 44 publications
2
41
0
Order By: Relevance
“…In this model, pigs treated with antibiotics plus GCs experienced, after 96 h of pneumonia onset, a decrease in the local inflammatory response compared to the other groups. Furthermore, animals treated with antibiotics plus GCs presented lower bacterial counts in both BALF and pulmonary tissue obtained at the end of the study, a finding that was related to a tendency to suffer from less-severe lesions, as revealed by a histopathological study [33]. In this sense, MEDURI et al [34] have demonstrated, in an in vitro study, that certain bacterial strains possess receptors for the cytokines IL-1b and TNF-a, and that the exposure of bacteria to these cytokines enhances their growth and virulence.…”
Section: Role Of Glucocorticosteroids In Severe Pneumoniamentioning
confidence: 87%
“…In this model, pigs treated with antibiotics plus GCs experienced, after 96 h of pneumonia onset, a decrease in the local inflammatory response compared to the other groups. Furthermore, animals treated with antibiotics plus GCs presented lower bacterial counts in both BALF and pulmonary tissue obtained at the end of the study, a finding that was related to a tendency to suffer from less-severe lesions, as revealed by a histopathological study [33]. In this sense, MEDURI et al [34] have demonstrated, in an in vitro study, that certain bacterial strains possess receptors for the cytokines IL-1b and TNF-a, and that the exposure of bacteria to these cytokines enhances their growth and virulence.…”
Section: Role Of Glucocorticosteroids In Severe Pneumoniamentioning
confidence: 87%
“…Other findings from this meta-analysis support the plausibility of the beneficial effects of corticosteroids in patients admitted for CAP: (I) the effect seems to increase with the severity of CAP, with a significant mortality benefit observed in trials that met pre-specified criteria for severe CAP (i.e., when at least 70% of patients enrolled had severe CAP at baseline, and/or when mortality was at least 15% in the control group), but not in trials that enrolled less severe CAP (15); (II) adjuvant corticosteroids were also associated with reductions in the need for mechanical ventilation (RR =0.45; 95% CI, 0.26-0.79), with an estimated number needed to treat of approximately 20 to avoid one requirement for mechanical ventilation, the development of acute respiratory distress syndrome (RR =0.24; 95% CI, 0.10-0.56), the time to clinical stability (mean difference, −1.22 days; 95% CI, −2.08 to −0.35 days), and the duration of hospitalization (mean difference, −1.00 days; 95% CI, −1.79 to −0.21 days); (III) these benefits were observed at a reasonable cost: a moderate increased in the frequency of hyperglycemia requiring treatment (RR =1.49; 95% CI, 1.01-2.19), but no excess of gastrointestinal haemorrhage (15). Of note, most trials did not observe any signal of an increased risk of infectious complications, which suggests, as was inferred from animal studies (21), that a short course (<7 days) of corticosteroids has probably no deleterious effect on the control of bacterial CAP, provided an adequate antibacterial treatment is administered concomitantly.…”
mentioning
confidence: 84%
“…And third, our cohort did not have information regarding the indication, dose, duration, and stopping of SCS. These are important since there are studies reporting that if given for a short period of time, the right dose may be favorable and result in an attenuated inflammatory response [Garcia-Vidal et al 2007;Agusti et al 2003;Sibila et al 2008b]. Further studies should consider measuring inflammatory biomarkers when assessing immunomodulatory agents such as SCS.…”
Section: Discussionmentioning
confidence: 99%